Novel phenotypic variant in the MYH7 spectrum due to a stop-loss mutation in the C-terminal region: a case report - Bánfai, Zsolt; Hadzsiev, Kinga; Pál, Endre; Komlósi, Katalin; Melegh, Márton; Balikó, László; Melegh, Béla (BMC medical genetics, 2017)
Background Defects of the slow myosin heavy chain isoform coding MYH7 gene primarily cause skeletal myopathies including Laing Distal Myopathy, Myosin Storage Myopathy and are also responsible for cardiomyopathies. Scapuloperoneal and limb-girdle muscle weakness, congenital fiber type disproportion, multi-minicore disease were also reported in connection of MYH7 . Pathogeneses of the defects in the head and proximal rod region of the protein are well described. However, the C-terminal mutations of the MYH7 gene are less known. Moreover, only two articles describe the phenotypic impact of the elongated mature protein product caused by termination signal loss. Case presentation Here we present a male patient with an unusual phenotypic variant of early-onset and predominant involvement of neck muscles with muscle biopsy indicating myopathy and sarcoplasmic storage material. Cardiomyopathic involvements could not be observed. Sequencing of MYH7 gene revealed a stop-loss mutation on the 3-prime end of the rod region, which causes the elongation of the mature protein. Conclusions The elongated protein likely disrupts the functions of the sarcomere by multiple functional abnormalities. This elongation could also affect the thick filament degradation leading to protein deposition and accumulation in the sarcomere, resulting in the severe myopathy of certain axial muscles. The phenotypic expression of the detected novel MYH7 genotype could strengthen and further expand our knowledge about mutations affecting the structure of MyHCI by termination signal loss in the MYH7 gene.